The Role of Past Climatic Variability in Fluvial Terrace Formation, a Case Study from River Mureş (Maros), Romania - Tamás Bartyik; Petru Urdea; Tímea Kiss; Alexandru Hegyi; György Sipos (Quaternary, 2023)
Fluvial terrace formation is a complex process governed by the interplay of climatic and tectonic forcings. From a climatic perspective, an incision is usually related to climatic transitions, while valley aggradation is attributed to glacial periods. We have reconstructed the formation of Late Pleistocene fluvial terraces along the middle, mountainous section of a temperate zone river (Mureş/Maros) in order to identify the roles of different climatic periods and potential vertical displacement in terrace development. Investigations were based on two profiles representing two different terrace levels. The profiles were subjected to sedimentological and detailed geochronological analyses using optically stimulated luminescence (OSL). The results indicated that the investigated terraces represent different incision events coinciding with climatic transition periods. However, a joint MIS 3 valley aggradation period can be identified at both of them. Thus, the relatively mild but highly variable climate of the MIS 3 facilitated sediment mobilization from upland catchments. On the other hand, there is no evidence of aggradation under the cold and stable climate of MIS 2. However, the tectonic setting favours incision at the site. Based on our results, we concluded that the timing of the main events was controlled primarily by climatic forcing. The terrace formation model recognised might also be applied at other rivers in the region.